Co‐Occurrence and Characteristics of Patients With Axial Spondyloarthritis Who Meet Criteria for Fibromyalgia: Results From a UK National Register. Issue 11 (27th October 2017) - Macfarlane, Gary J.; Barnish, Maxwell S.; Pathan, Ejaz; Martin, Kathryn R.; Haywood, Kirstie L.; Siebert, Stefan; Packham, Jonathan; Atzeni, Fabiola; Jones, Gareth T.
Abstract : Objective: To estimate the proportion of patients with axial spondyloarthritis (SpA) in a UK national biologics registry who met criteria for fibromyalgia (FM), and to delineate the characteristics of these patients. Methods: Two cohorts of patients are prospectively recruited from across 83 centers in the UK for the British Society for Rheumatology Biologics Register in Ankylosing Spondylitis (BSRBR‐AS). All patients are required to meet Assessment of SpondyloArthritis international Society (ASAS) criteria for axial SpA. Patients are either newly starting biologic therapy (biologics cohort) or are naive to treatment with biologic agents (non‐biologics cohort) at the time of recruitment, and all patients are followed up prospectively. At recruitment and follow‐up, clinical information and measurements are recorded while patients complete the 2011 research criteria for FM and assessments of the level of disease activity and work impact. Results: Of the patients registered in the BSRBR‐AS, 1, 504 (68% male) were eligible for the current analysis, of whom 311 (20.7%) met the 2011 research criteria for FM. Prevalence of FM was similar between patients who fulfilled the modified New York criteria for AS (19.7%) and those who fulfilled ASAS imaging criteria but not the modified New York criteria (25.2%); however, among those who fulfilled only the ASAS clinical criteria, the prevalence of FM was lower (9.5%). Patients who met FM criteria reported significantly worse disease activity, function, global severity scores, and quality of life, and were more likely to have moderate or severe levels of mood disorder and clinically important fatigue. Patients who met FM criteria reported experiencing work impairment around half their working time. Meeting FM criteria was not related to elevated C‐reactive protein levels or most extraspinal manifestations, but was associated with a higher likelihood of having received biologic therapy. Conclusion: Developing management approaches that would address the significant unmet clinical needs of the 1 in 5 patients with axial SpA who meet criteria for FM should be a research priority.